DESIGN OF ITEM LAYOUT WITH SHARE STORAGE METHOD AT PT. SISTAMA PARTNER - Muhammad Arif Hernawan; Siska Amonalisa; Johanes Kurniawan Liauw; Indra Kurniawan (ABNUS Publisher, 2022)
Warehouses are used to store company-owned goods, both raw materials and finished goods. Good warehouse conditions can help carry out all activities in the company. According to. Therefore, design patterns and warehouse layouts are very important to simplify and increase company productivity. The use of storage methods and warehouse management systems that have less effect on the operations and smooth running of the goods. so that all operational activities run smoothly. The use of the correct storage method can also maximize the existing warehouse capacity. With warehouse conditions that are not well organized, it also has an impact on the less than optimal order processing because the location of the goods is not organized and orderly. The application of this method is a shared storage method because by applying this method the distance of taking ordered goods is faster. That way you can increase the total order that can be completed